Navigating the blurred work-life boundary under the hybrid working context: how the appraisal of emotions prompts individual boundary management tactics - Xu, Mengyi; Wang, Lu (British Academy of Management, 2023)
Hybrid working heightens work-life boundaries blurring. This can create the need for employees to constantly navigate evolving demands in their work-nonwork environment, often before formalized strategic, organisational, and managerial interventions are developed and/or implemented. Therefore, understanding why and how adapt to boundary blurs and manage their work-life balance is critical for effective hybrid working. Drawn on appraisal theories of emotion, we argue that employees' appraisals of boundary-blurring situations can elicit emotions, which prompt employees to navigate and adapt to their blurred boundaries in their work-life balance. We substantiate this with a longitudinal one-month dairy and post-interview study using a sample of 34 employees in the UK Higher Education (HE) sector, where hybrid working has been widely applied. Our finding unveils that both positive and negative emotions help the individual efficiently respond to boundary blurring, using prevention- and promotion-oriented tactics; the former associated with negative emotions focuses on the temporary work-life blurring, whereas the latter associated with positive emotions that attempts to leverage resources and opportunities for long term work-life balance. The findings make practical implications for employees and organisations on how to effectively manage hybrid working by understanding work-life boundaries.
Keywords: Work-life balance; Boundary management tactics; Emotion; Hybrid working; Qualitative diary studies